The poetry of Statius - Dam, Harm-Jan van, 1948-; Nauta, Ruurd R.; Smolenaars, Johannes Jacobus Louis. (Mnemosyne, Supplements, 2008)
The Roman poet P. Papinius Statius (ca. 45-96) is the author of two epics (the Thebaid and the unfinished Achilleid ) and a large corpus of occasional verse ( Silvae ). This poetry, long seen as derivative or decadent, is increasingly appreciated for the daring and originality of its responses both to the Greek and Latin literary tradition and to the contemporary Roman world. This volume offers the papers delivered at a symposium on Statius (Amsterdam 2005) by leading scholars in the field from Europe and North America. These papers demonstrate the fascination of Statius' poetry on account of the poet's vast knowledge of Greek and Latin tragedy, his rapid narrative, psychological acumen, brilliant eulogies, and pessimistic views on gods and men. The focus of the collection is on literary technique in the Thebaid , on socio-historical aspects of the Silvae , and on the reception of Statius in European literature and scholarship.